الإعلام والتحول الديمقراطي - عوفي, مصطفى; بلوصيف, الطيب (Sciences de l'Homme et de la Société, 2014)
تعتبر وسائل الإعلام من المؤسسات الرئيسية في تشكيل الرأي العام الذي يعمل على ترسيخ القيم الديمقراطية من خلال القدرة على خلق قيم ثقافية جعلته يشكل منبرًا أساسيًا في التسويق للقيم الديمقراطية وحرية التفكير، فهو مؤسسة تسهر على تنوير الرأي العام الذي يعتبر السلطة الحقيقية في المجتمع، وساعد في تعظيم هذه الوظائف وتنويعها التطور الحاصل في تكنولوجيات الاتصال من الوظيفة الكلاسيكية في نقل الأخبار إلى المساهمة في نقل المجتمعات من أنظمة تسلطية إلى أنظمة ديمقراطية.   The media is one of the key institutions in the formation of public opinion, which works to entrench democratic values through the ability to create cultural values. Media has become a key marketing platform for the values of democracy and freedom of thought, It ensures the Foundation to enlighten public opinion, which is the real power in society. The evolution in the technologies of communication in the classic function of the news to contribute to the transfer of communities from authoritarian regimes to democratic regimes, helped to expand and diversity of the functions of the media.